Historical Theories - Umair Awan, Umair Ali (sourcecoder, 2022)
This article will help to understand history and it’s theories. It will also elaborate the opinion historics had about history, for whom history was written about and who become the center of it after revolution. Historical change occurs constantly which include major and minor events following the historical changes took place in the process of cause and effect is discussed in this particular work.